Evaluation of the Oral Hygiene Status of Patients with Type 2 Diabetes Mellitus Who Use Partial Removable Prosthetics (Clinical and Laboratory Study) - Zakharova Г. Є.; Skibitskyi В. С. (Actual Dentistry, 2025)
Summary. The study is devoted to the comparative evaluation of clinical, hygienic, and microbiological indicators of oral cavity condition in individuals with type 2 diabetes mellitus who use partial removable prostheses made of different materials. Prosthetic treatment was performed on 83 patients with partial tooth loss and compensated type 2 diabetes, with subsequent dispensary observation for a year. Patients used prostheses made of four types of materials—polyamide, РММА of chemical polymerization, monomer-free, and combined from cobalt-chromium alloy and monomer-free РММА. Aim: to investigate the improvement of the quality of prosthetics with partial removable structures in patients with type 2 diabetes mellitus through a clinically and laboratory-based approach to the selection of basic prosthetic materials. Material and methods. Depending on the material of the dentures, patients were divided into four groups. To study the influence of denture materials on the hygienic condition of the oral cavity, index assessment methods were used. To assess the ability of oral microflora to accumulate and colonize on the surface of removable dentures, a comparative experimental microbiological study was conducted with samples of four types of base materials. Results. It was found that in long-term follow-up, the best level of hygiene and the lowest level of bacterial contamination on the prosthesis surface were observed with dentures made of cobalt-chromium alloy and monomer-free PMMA. Conclusions. The structural features and chemical properties of prosthetic materials can impact the hygienic status of the oral cavity. For prosthetics of patients with type 2 diabetes mellitus, it is recommended to choose materials with better hygienic indicators.